Public Perception of Flood Mitigation Projects in the Coastal Villages - Ismawaty, Andi (Generasi Sains Indonesia, 2024)
mitigation projects in the coastal villages of Dumai, Riau Province, Indonesia, with a focus on how social, cultural, and economic factors influence participation and perceived effectiveness. A qualitative approach was employed using semi-structured interviews, focus group discussions, and field observations involving 25 participants selected through purposive sampling. Data were analyzed using thematic analysis to identify key patterns and relationships. The findings reveal that while structural mitigation measures, such as embankments and drainage systems, have reduced flood intensity, their long-term effectiveness is constrained by inadequate maintenance, unequal distribution of benefits, and limited community involvement. Community participation emerges as a critical mediating factor that shapes both the sustainability and acceptance of mitigation efforts. Furthermore, social cohesion, cultural compatibility, and economic capacity significantly influence how communities engage with and evaluate these projects. The study contributes to the literature by proposing an integrated conceptual framework that links contextual factors, participation, and perceived effectiveness in a coastal setting. The results suggest that flood mitigation strategies should adopt a more inclusive, culturally sensitive, and economically sustainable approach to enhance resilience in vulnerable coastal communities.